Effectiveness of Direct Oral Anticoagulants in Obese Adults With Atrial Fibrillation: A Systematic Review of Systematic Reviews and Meta-Analysis - Shaikh, Fahad; Wynne, Rochelle; Castelino, Ronald L.; Inglis, Sally C.; Ferguson, Caleb (Frontiers in Cardiovascular Medicine, 2021)
Background Atrial Fibrillation (AF) is the most common sustained cardiac arrhythmia. Obesity is an independent risk factor for AF. Anticoagulants have been strongly recommended by all international guidelines to prevent stroke. However, altered pathophysiology in obese adults may influence anticoagulant pharmacology. Direct oral anticoagulants (DOACs) in the context of obesity and AF have been examined in recent systematic reviews. Despite the similarities in included studies, their results and conclusions do not agree. Methods and Results The protocol for this review was registered with PROSPERO (CRD42020181510). Seven key electronic databases were searched using search terms such as “atrial fibrillation”, “obese*”, “overweight”, “novel oral anticoagulant”, “direct oral anticoagulant”, “DOAC”, “NOAC”, “apixaban”, dabigatran”, “rivaroxaban” and “edoxaban” to locate published and unpublished studies. Only systematic reviews with meta-analyses that examined the effect of DOACs in overweight or obese adults with AF, published in the English language, were included. A total of 9,547 articles were initially retrieved. After removing the duplicates, title and abstract review and full-text review, five articles were included in the systematic review. From these only RCTs were included in the meta-analyses. There was disagreement within the published systematic reviews on DOACs in obesity. The results from our meta-analysis did not show any significant difference between all body mass index (BMI) groups for all outcomes at both 12 months and for the entire trial duration. Non-significant differences were seen among the different types of DOACs. Conclusion There was no difference between the BMI classes in any of the outcomes assessed. This may be due to the limited number of people in the trial that were in the obese class, especially obese class III. There is a need for large prospective trials to confirm which DOACs are safe and efficacious in the obese class III adults and at which dose.